Familial effects on youth smoking in Brazil - Alberto Palloni; Laeticia Rodrigues de Souza; Letícia Junqueira Marteleto (International Policy Centre for Inclusive Growth (IPC-IG), 2016)
As with many other addictions and risk behaviours, smoking initiation is an early affair: most who adopt it at all do so early on during adolescence, rarely beyond their mid-20s. It is known that the cumulative health and mortality effects of smoking take a long time to unfold (Gajalakshmi et al. 2000; WHO 2008) and that they are a direct result of all three components of the behaviour: age of initiation, duration and intensity. Because age of initiation influences the other two components, the cumulative physiological damage induced by smoking depends on events that take place early in life and over a very small period of time. Protecting this sensitive period could not only remove the risk of ever smoking altogether but might also weaken the intensity and improve chances of desistance among those who do start smoking. For the majority of young people, most of the exposures that contribute to early smoking uptake are strongly associated with familial conditions and environments. [...]
Keywords: 330; familial effects; youth smoking; Brazil